Restoring trust within relations in a local faith community : a pastoral study towards sustainable reconciliation in a TRC era - Manuel, Ashwin Sherman (Stellenbosch : Stellenbosch University, 2021)
Thesis (MTh)--Stellenbosch University, 2021.